Current situation and future perspectives for textile effluent decolourisation - Soares, Graça M. B. (2004)
Textile dyes are an important class of synthetic organic compounds and are therefore common industrial pollutants. They are produced in large scale and may enter the environment during production or later on during fibre dyeing. Due to the stability of modern dyes, conventional biological (activated sludge) treatment methods for industrial wastewater are ineffective, resulting in an intensively coloured discharge from the treatment facilities. Thus, there is a need for developing treatment methods that are more effective in eliminating dyes from waste stream at its source. In the present work we review existing processes as well as promising new technologies for textile wastewater decolourisation. Particular emphasis is given to biotechnological and advanced oxidative processes. Results using the latter methodology are presented as such processes are highly efficient and simple to operate.